xcess Weight and Physical Activity in Nursing Students of a University in the North of Lima: Exceso de peso y actividad física en estudiantes de enfermería de una universidad del norte de Lima - Acuña-Medina, Liseth (2019)
Objectives. Determine the frequency of excess weight and the level of physical activity in nursing students. Materials and methods. The study was cross-sectional descriptive. Nursing students from a private university in the North of Lima participated. Excess weight was determined by the body mass index and physical activity (AF) using the short version of the International Physical Activity Questionnaire (IPAQ). Results. Participants were 174 students of both sexes with an average age of 23.7 years (SD = 6.9, min 16, max 58). Of the sample, 83.9% (n = 146) were women, 58.6% (n = 102) were in the first year of study, 79.9% (n = 139) were single, 63.2% (n = 110) worked, 74.7% (n = 130) without children, 54.6% (n = 95) had a family member who practiced sports. Of the sample, 28.7% (n = 50) were overweight and 6.3% (n = 11) were obese. Regarding AF, 25.9% (n = 45) showed low physical activity, 31% (n = 54) moderate and 43.1% (n = 75) showed high level. The level of AF occurred in a greater proportion in the female sex (p = 0.041). Conclusions. In the present study, more than a third of the nursing students were overweight and more than half had insufficient physical activity, the low level of physical activity was mainly female. Key words: Obesity; Overweight; Students, Nursing;, Peru (Source: MeSH, NLM).